M-mode Diagnosis of Tachyarrhythmia Can be Erroneous Owing to "Pseudo 1:1 Atrioventricular Movement" of the Atrial Wall Adjacent to the Atrioventricular Valve Possibly due to Atrioventricular Constraint: A Case of Neonatal Atrial Flutter With 2:1 Atrioventricular Conduction. Issue 12 (17th April 2018) - Kawano, Akiko; Oshima, Ayumi; Masutani, Satoshi; Ishiguro, Akio; Iwamoto, Yoichi; Ishido, Hirotaka; Taketazu, Mio; Senzaki, Hideaki
M-mode echocardiography has been playing an important role in the diagnosis of fetal tachyarrhythmia. We recently encountered a neonatal case of atrial flutter with 2:1 atrioventricular conduction. However, M-mode erroneously indicated 1:1 atrioventricular movement. While the movement of the atrial wall far from the atrioventricular valve was much faster than that of the ventricular wall, the atrial wall adjacent to the atrioventricular valve fully synchronized to that of the ventricular wall. Thus, to avoid this novel pitfall, it would be important to add an additional assessment focusing on the movement of the atrial wall far from the ventricle.